ANALYSIS AND SYNTHESIS OF SUBSCRIBER ACCESS DIGITAL SYSTEMS. CONDITION AND PROSPECTS - V. I. Kirillov; A. I. Belko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Briefly main results of the researches on analysis and structured-parametric syntheses of digital systems of subscriber access, which were got in BSUIR, are stated. The main trends of researches are indicated and the variants of the structured-parametric syntheses of the digital systems, which use different technologies of transmition and telecommunications networks buildings, are represented. The analysis of the received results was done and the recommendations on practical use was developed on the grounds of this analysis. The trends for perspective researches are formulated.